EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN NUMBERED HEADS TOGETHER PADA POKOK BAHASAN BANGUN RUANG SISI DATAR DITINJAU DARI KECERDASAN INTERPERSONAL SISWA KELAS VIII SMP NEGERI DI KOTA MADIUN - Ayu Kurniawati, Kiki Riska; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The aims of this research were to find out the different effect of each categories of learning model, students interpersonal intelligence and their interaction towards students mathematics learning achievement on the subject of plane geometry. The research was quasi experimental with 3Ã3 factorial design. The population was all students of grade VIII State Junior High School in Madiun City on the second semester of 2013/2014 academic years. Sampling was done by stratified cluster random sampling technique. The sample of this research consisted of the students of SMP N 3 Madiun, SMPN 7 Madiun, and SMPN 10 Madiun. The sample consisted of 260 students. The hypothesis test used unbalanced two ways analysis of variance at the significance level of 0,05. Based on hypothesis test, it can be concluded that: (1) the cooperative learning model of Jigsaw type gives a better mathematics achievement than cooperative learning model of NHT type and direct learning model, and the cooperative learning model of NHT type gives a better mathematics achievement than direct learning model; (2) students with the high interpersonal intelligence had the same achievement as students with the medium interpersonal intelligence, students with the high interpersonal intelligence had better achievement than students with the low interpersonal intelligence and the students with the medium interpersonal intelligence had the same achievement as students with the low interpersonal intelligence; (3) on the cooperative learning model of Jigsaw type, NHT type and direct learning model, students with the high interpersonal intelligence had the same achievement as students with the medium interpersonal intelligence, students with the high interpersonal intelligence had better achievement than students with the low interpersonal intelligence and the students with the medium interpersonal intelligence had the same achievement as students with the low interpersonal intelligence; and (4) on students interpersonal intelligence high, medium and low, the cooperative learning model of Jigsaw type gives a better mathematics achievement than cooperative learning model of NHT type and direct learning model, and the cooperative learning model of NHT type gives a better mathematics achievement than direct learning model.Keywords:Â Jigsaw, NHT, interpersonal intelligence